A64 HOSPITALIZATION IN INFLAMMATORY BOWEL DISEASE: A POPULATION-BASED COMPARISON OF DEFINITIONS. (26th February 2020) - Coward, S; Benchimol, E I; Bernstein, C N; Bitton, A; Carroll, M W; Jelinski, S; Jones, J; Kuenzig, E; Leddin, D; Murthy, S; Nguyen, G C; Otley, A; et al.
Abstract: Background: Most administrative studies of hospitalization in inflammatory bowel disease (IBD) use two definitions: IBD in any diagnostic position (IBD-ANY), and IBD as the most responsible diagnostic (IBD-MRD). There is a third less commonly used definition: total hospitalization; this definition captures all hospitalizations of prevalent IBD patients and therefore it can give a more realistic picture of the burden of IBD. Aims: To compare differing definitions (total, IBD-ANY, and IBD-MRD) of hospitalizations. Methods: A previously defined population-based IBD prevalent cohort for Alberta (n=30, 698) was used to pull all hospital admissions from the Discharge Administrative Database (DAD; 2002–2015). Three hospitalization definitions were used: i. Total (all hospitalizations of prevalent cohort independent of presence of code for IBD); ii. IBD-ANY (code for IBD [K50.x; K51.x] contained in any diagnosis field); and, iii. IBD-MRD (most responsible diagnosis was IBD). Age- and sex- standardized rates (2015 Canadian population) were calculated using the prevalent population. Log-linear regression was performed to calculate Average Annual Percentage Change (AAPC) with associated 95% confidence intervals (CI) of each type of hospitalization. We assessed the top five most common most-responsible diagnosis codes for hospitalizations that were contained in the total hospitalizations but not an IBD-ANY hospitalization. Results: From 2002 to 2015, 63.5% of IBD prevalent patients in AB had ≥1 hospitalization; 44.2% had ≥1 IBD-ANY hospitalization; 28.6% had ≥1 IBD-MRD hospitalization; and, 40.6% had a hospitalization that did not contain a code for IBD. All hospitalization rates decreased significantly over time. Of the top five most common most responsible diagnosis, contained in admissions that were not IBD-ANY, three were gastroenterological: i. K52.9 (non-infective gastroenteritis); ii. A09.9 (diarrhea and gastroenteritis of presumed infectious origin); and, iii. Z43.2 (attention to ileostomy). Conclusions: Total hospitalizations is an important measure to report since accounting for all hospitalizations of IBD patients is necessary in order to allocate healthcare resources appropriately. To be able to ensure these patients receive the care they need we need to be able to accurately assess the true burden of IBD. Funding Agencies: CIHR